Pope Francis and American Economics - Cloutier, David (Horizons, 2015)
Reaction among conservatives to Pope Francis' Evangelii Gaudium has most often been negative. Ross Douthat, however, in his 2013 New York Times op-ed, has offered a more nuanced critique. Our four Roundtable authors respond to Douthat's implied invitation to a discussion by responding from the viewpoint of Catholic social thought.